Integrative Systematic Literature Review: Quantitative and Qualitative Approaches in Interventions to Reduce Self-Harm Behaviour in Adolescents - Alini Alini; Faridah Mohd Said; Nia Aprilla; Bri Nofrika (Journal of Public Health Indonesian, 2026)
Self-harm behaviour in adolescents is a crucial mental health issue that increases the risk of suicide and requires effective intervention. Psychological approaches such as the Transtheoretical Model (TTM), Cognitive Behavioural Therapy (CBT), Dialectical Behaviour Therapy (DBT), and digital technology have been used to reduce this behaviour, but a deep understanding of the adolescent experience is also necessary. This systematic review aims to evaluate the efficacy of interventions to reduce self-harming behaviour in adolescents by integrating quantitative research results and qualitative insights related to motivation, social factors, and the process of stopping the behaviour. A literature search using the PICO strategy was conducted in the Scopus, PubMed, EBSCO, and ScienceDirect databases. Article selection followed the PRISMA method with inclusion criteria of 2015–2024, full text, open access, and English language. Quantitative studies included RCT and longitudinal studies, while qualitative studies used in-depth interviews and thematic analysis. Data synthesis from both approaches was conducted narratively and through thematic meta-synthesis. From 116 articles assessed for eligibility, a total of 8 studies met the inclusion criteria, consisting of 5 quantitative and 3 qualitative studies. Quantitative findings indicate that psychological interventions significantly reduce the frequency of self-harm behaviour. Qualitative findings highlight key factors such as difficulties in emotional regulation, social pressure, barriers to help-seeking, and the importance of family support. The tension between adolescent autonomy and the need for social support emerged as a central theme.. A multifaceted approach that integrates evidence-based therapy with an understanding of the psychosocial context effectively reduces self-harming behaviour in adolescents. Recommendations point towards culturally sensitive family- and school-based interventions and further research using mixed methods.